Assessing social-emotional development in children from a longitudinal perspective. (19th December 2008) - Denham, S A; Wyatt, T M; Bassett, H H; Echeverria, D; Knox, S S
Abstract : This paper provides an overview of methodological challenges related to the epidemiological assessment of social-emotional development in children. Because population-based studies involve large cohorts and are usually multicentre in structure, they have cost, participant burden and other specific issues that affect the feasibility of the types of measures that can be administered. Despite these challenges, accurate in-depth assessment of social-emotional functioning is crucial, based on its importance to child outcomes like mental health, academic performance, delinquency and substance abuse. Five dimensions of social-emotional development in children are defined: (1) social competence; (2) attachment; (3) emotional competence; (4) self-perceived competence; and (5) temperament/personality. Their measurement in a longitudinal study and associated challenges are discussed. Means of making valid, reliable assessments while at the same time minimising the multiple challenges posed in the epidemiological assessment of social-emotional development in children are reviewed.